1983
DOI: 10.1152/jappl.1983.54.2.562
|View full text |Cite
|
Sign up to set email alerts
|

Reflex control of breathing following inhalation of cigarette smoke in conscious dogs

Abstract: The acute ventilatory response to spontaneously inhaled cigarette smoke (750 ml, 10% concentration) was studied in 92 experiments on 6 awake resting dogs. Upon the first or second breath of smoke inhalation, either an apnea or an augmented breath was elicited consistently in each dog, and a hyperpnea occurred subsequently. Minute ventilation (VE) increased from a base line of 3.2 to a peak of 23.9 l/min at 8.3 s (mean values) after the smoke was completely inhaled and returned toward base line in 1-3 min. Cold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Whereas, coughing was absent with inhalation of both low nicotine and gas phase irritants. This corroborated their findings in the dog model (Lee et al, 1983(Lee et al, , 1985(Lee et al, , 1986(Lee et al, , 1989Kou & Lee, 1990. The second study assessed the role of nicotine in TS-associated airway irritation and cough.…”
Section: Mechanisms Of Action Of Ts In Acute Cough 321 Nicotinic Resupporting
confidence: 71%
See 1 more Smart Citation
“…Whereas, coughing was absent with inhalation of both low nicotine and gas phase irritants. This corroborated their findings in the dog model (Lee et al, 1983(Lee et al, , 1985(Lee et al, , 1986(Lee et al, , 1989Kou & Lee, 1990. The second study assessed the role of nicotine in TS-associated airway irritation and cough.…”
Section: Mechanisms Of Action Of Ts In Acute Cough 321 Nicotinic Resupporting
confidence: 71%
“…Using single fibre analysis, the authors observed that a single puff of TS generated from high nicotine, but not low nicotine cigarettes triggered action potential generation in bronchopulmonary C-fibres and RARs. Moreover, the competitive selective nACh receptor antagonist hexamethonium inhibited sensory nerve stimulation in response to TS, but had no effect on other tussive stimuli, indicating a role for nicotine in the smokeinduced irritant response in dogs (Lee et al, 1983(Lee et al, , 1985(Lee et al, , 1986(Lee et al, , 1989Kou & Lee, 1990. The ability of nicotine to stimulate airway sensory nerves was corroborated in rat isolated vagal ganglia neurons by assessing calcium influx.…”
Section: Mechanisms Of Action Of Ts In Acute Cough 321 Nicotinic Rementioning
confidence: 96%
“…For example, in awake dogs inhalation of cigarette smoke via tracheostomy tube immediately evoked augmented breaths in approximately 30% of the animals tested (6). In contrast, when the same smoke inhalation challenge was applied to the same animals under anesthesia, pulmonary chemoreflexes (apnea, bradycardia, and hypotension) were the only responses found and augmented breaths were almost never observed (5,6). This discrepancy suggests that suppression of the central nervous system by anesthetics may have affected the interaction of these afferents and depressed the reflex response mediated through the activation of RARs to a larger degree.…”
Section: Airway Afferents Involved In the Reflex Responses To Inhaledmentioning
confidence: 96%
“…Several recent studies have attempted to uncover the mechanisms underlying the interaction between the pulmonary C fibers and RARs in the overall regulation of the defense reflex responses. Inhalation of cigarette smoke, a common inhaled irritant in human airways, has been shown to elicit irregular breathing pattern, cough reflex, and bronchoconstriction in a number of species including humans (5)(6)(7)(8)(9). Although it is believed that most of these responses are mediated through the activation of these two types of vagal afferents, the relative contributions of these two types of afferents to the emergence of these reflex responses are not known.…”
Section: Airway Afferents Involved In the Reflex Responses To Inhaledmentioning
confidence: 99%